2019
DOI: 10.1210/jc.2019-01182
|View full text |Cite
|
Sign up to set email alerts
|

Three Discrete Patterns of Primary Aldosteronism Lateralization in Response to Cosyntropin During Adrenal Vein Sampling

Abstract: Context Cosyntropin [ACTH (1–24)] stimulation during adrenal vein (AV) sampling (AVS) enhances the confidence in the success of AV cannulation and circumvents intraprocedure hormonal fluctuations. Cosyntropin’s effect on primary aldosteronism (PA) lateralization, however, is controversial. Objectives To define the major patterns of time-dependent lateralization, and their determinants, after cosyntropin stimulation during AVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 41 publications
4
40
1
Order By: Relevance
“…However, almost all patients had repeat biochemical testing to assess for a biochemical cure. Evaluation for somatic mutations in the resected lesions may be interesting in light of recent study findings that the underlying genetic mutation determines the response of LI to ACTH, with KCNJ5 mutations associated with descending LI, while ATP1A1 and ATP2B3 mutations associated with an ascending LI 32 . Ongoing research which explores alternative strategies, such as nuclear medicine imaging and venous steroid profiling, for subtyping in the setting of discordant AVS results will also facilitate the accurate diagnosis of unilateral versus bilateral PA.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost all patients had repeat biochemical testing to assess for a biochemical cure. Evaluation for somatic mutations in the resected lesions may be interesting in light of recent study findings that the underlying genetic mutation determines the response of LI to ACTH, with KCNJ5 mutations associated with descending LI, while ATP1A1 and ATP2B3 mutations associated with an ascending LI 32 . Ongoing research which explores alternative strategies, such as nuclear medicine imaging and venous steroid profiling, for subtyping in the setting of discordant AVS results will also facilitate the accurate diagnosis of unilateral versus bilateral PA.…”
Section: Discussionmentioning
confidence: 99%
“…African American patients with APAs commonly harbor CACNA1D mutations [29]. We found that, overall, patients with CACNA1D-mutated APAs had the least predictable impact of cosyntropin on the lateralization index [42], which could explain, at least in part, the higher proportion of discordant AVS results in this population. Stratified PA subtyping combining AVS results from both pre-and post-cosyntropin stimulation, revealed that cases consistently classified as unilateral had the highest adrenal vein and peripheral aldosterone concentrations, and the most profound contralateral suppression [42].…”
Section: Steroid Profiling As a Tool For Pa Subtypingmentioning
confidence: 71%
“…We found that, overall, patients with CACNA1D-mutated APAs had the least predictable impact of cosyntropin on the lateralization index [42], which could explain, at least in part, the higher proportion of discordant AVS results in this population. Stratified PA subtyping combining AVS results from both pre-and post-cosyntropin stimulation, revealed that cases consistently classified as unilateral had the highest adrenal vein and peripheral aldosterone concentrations, and the most profound contralateral suppression [42]. As the impact of cosyntropin on autonomous vs. normal aldosterone-producing cells remains elusive, cases with inconsistent lateralization might represent either small APAs or asymmetrical BHA.…”
Section: Steroid Profiling As a Tool For Pa Subtypingmentioning
confidence: 79%
See 2 more Smart Citations